2022
DOI: 10.1101/2022.11.22.517512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mechanism of RanGTP priming H2A-H2B release from Kap114 in an atypical RanGTP•Kap114•H2A-H2B complex

Abstract: Previously we showed that the nuclear import receptor Importin-9 wraps around the H2A-H2B core to chaperone and transport it from the cytoplasm to the nucleus (Padavannil et al. 2019). However, unlike most nuclear import systems where RanGTP dissociates cargoes from their importins, RanGTP binds stably to the Importin-9•H2A-H2B complex and formation of RanGTP•Importin-9•H2A-H2B facilitates H2A-H2B release to the assembling nucleosome (Padavannil et al. 2019). Here we show cryo-EM structures of Importin-9•RanGT… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(23 citation statements)
references
References 79 publications
3
20
0
Order By: Relevance
“…Biochemical and structural studies of binary Kap114-H2A-H2B and Nap1 2 -H2A-H2B interactions, and pull-down studies of Kap114 and Nap1 from yeast lysates have been reported (13,22,36,41). First, we confirmed the previous findings using analytical ultracentrifugation (AUC), size exclusion chromatography multi-angle light scattering (SEC-MALS) and pull-down binding assays with recombinant Kap114, Nap1 and H2A-H2B (SI Appendix, Fig.…”
Section: Kap114 Binds Simultaneously To a H2a-h2b Heterodimer And A N...supporting
confidence: 88%
See 2 more Smart Citations
“…Biochemical and structural studies of binary Kap114-H2A-H2B and Nap1 2 -H2A-H2B interactions, and pull-down studies of Kap114 and Nap1 from yeast lysates have been reported (13,22,36,41). First, we confirmed the previous findings using analytical ultracentrifugation (AUC), size exclusion chromatography multi-angle light scattering (SEC-MALS) and pull-down binding assays with recombinant Kap114, Nap1 and H2A-H2B (SI Appendix, Fig.…”
Section: Kap114 Binds Simultaneously To a H2a-h2b Heterodimer And A N...supporting
confidence: 88%
“…The superhelical Kap114 wraps around the H2A-H2B histone-fold domain (Fig. 1B), occluding the histone's DNA-binding surfaces and thus also acting as a histone chaperone (40,41). The Kap114•H2A-H2B complex is unusual in its interactions with the GTPase Ran GTP .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Additionally, Ran•GTP was found to form a complex with H2A-H2B and the histone chaperone importin 9 (as well as its yeast homologue Kap114) during nucleosome assembly. 53,54 In these ternary complexes, Ran•GTP modulates importin-histone interactions and makes transient contacts with α3 and αC of H2A. The complexation leads to a conformational change in importin 9/ Kap114 that promotes the release of H2A-H2B into the assembling nucleosome.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The complexation leads to a conformational change in importin 9/ Kap114 that promotes the release of H2A-H2B into the assembling nucleosome. As importin-9 binds to H2A-H2B via a mechanism also involving arginine interactions with the acidic patch as well as to Ran, 53,54 it is conceivable that, in the vicinity of chromatin, a high concentration of RCC1 may result in competition between importins and RCC1 for binding to both H2A-H2B and Ran. The Ran-nucleosome interactions mentioned above are not observed in our structure, which features Ran in its (mostly) nucleotide-free state (see below).…”
Section: ■ Results and Discussionmentioning
confidence: 99%